Per- and polyfluoroalkyl substances, vitamin D, and risk of preterm birth in a Canadian cohort - Mandy Fisher; James Owen; Leonora Marro; Beth Potter; Hope A. Weiler; Gillian England-Mason; Michael M. Borghese; Mark Walker; Linda Dodds; Michael Helewa; Tye E. Arbuckle; Bruce Lanphear; et al. (Environmental Research, 2026)

How Implementing the Rights of Wetlands Provides Benefits to People and Wetlands: Relationships, Rights, Responsibilities, Experiences, and Actions - Gillian Davies; Ritesh Kumar; M. Siobhan Fennessy; Nick Davidson; Kai Huschke; Dave Pritchard; Matthew Simpson; Priyanie Amerasinghe; William R. Moomaw; Erin Okuno; Bethanie Walder; Chaturangi Wickramaratne; et al. (Wetlands, 2026)
Rights of wetlands shifts the people-wetlands relationship towards one recognizing the intrinsic rights and living beingness of wetlands, embodying reciprocity, kinship, and gratitude. Recognition of wetland rights occurs within the broader Rights of Nature movement, which has often been led by Indigenous Peoples and local communities from many cultural traditions. Intrinsic wetland rights centre on the right to exist and incorporate seven other rights, forming a holistic framework that enables preservation of wetland ecosystem integrity. These rights provide the basis for a wetland’s thriving existence. The eight rights are: • the right to exist. • their natural place in the landscape; • natural and connected hydrologic regimes; • natural climatic conditions; • naturally occurring biodiversity; • natural ecosystem processes; • natural water, soil, and air quality (i.e., structural integrity and form); and. • regeneration and a naturally determined future. Moral and ethical responsibilities towards these rights include fostering harmonious relationships in and with wetlands, respecting interdependence of all wetland components, safeguarding and fostering conditions enabling rights of wetlands, and acting in a precautionary manner when faced with risks of harm to wetlands. Legal and policy responsibilities include acknowledging plural worldviews, recognising legal standing and political orientations to represent and defend wetland rights, providing adequate means for wetland representation and defending and advocating for wetlands, and using best available science to restore degraded wetlands and support regeneration, thereby supporting harmonious societal relationships with wetlands. Opportunities for implementation of rights of wetlands at a variety of scales (individual, community, national, and global) are explored, and training/guidance resources are referenced.

The Separate Roles of Vascular Plants and Sphagnum Mosses in Regulating the Net CO 2 Exchange in a Boreal Peatland During Key Phenological Phases - Antonia Hartmann; Kyohsuke Hikino; Lukas Guth; Gillian Simpson; Järvi Järveoja; Mats B. Nilsson; Matthias Peichl (Global Change Biology, 2026)
Boreal peatlands provide an important carbon store, which is highly susceptible to future changes in the global climate. Predictions of climate feedbacks on the peatland carbon balance require an in‐depth understanding of how vegetation dynamics and environmental conditions jointly govern the production and decomposition of organic matter. However, detailed knowledge on the separate roles of plant functional groups (PFGs) in regulating peatland production and respiration fluxes in response to various abiotic factors at sub‐seasonal scales is currently lacking. In this study, we used high‐temporal resolution CO 2 flux data from an automated chamber system established across experimental vegetation removal plots to separate the production and respiration fluxes of vascular plants and Sphagnum mosses over three growing seasons (2021–2023) in a boreal peatland. We found that gross primary production (GPP) of Sphagnum mosses exceeded that of vascular plants during green‐up (average ratio: 1.18) and senescence (1.11), whereas vascular plants were the main contributor during the peak season (0.88). Vascular plants dominated autotrophic respiration (RA; 78%–93%) in all phenophases and contributed 38%–40% to growing season ecosystem respiration. For both PFGs, plant phenology was the primary driver for variations in GPP during green‐up, whereas photosynthetic photon flux density was most important in regulating GPP during the peak season and senescence. Vascular plants reached greater maximum GPP throughout all phenophases, whereas Sphagnum mosses had a higher initial light use efficiency during green‐up and senescence. Moss RA exhibited greater daytime temperature sensitivity than vascular plants during the peak season and senescence, but not during nighttime. These findings highlight that climate change effects on vegetation phenology and composition may strongly alter the peatland carbon cycle. Thus, understanding the separate roles of vascular plants and Sphagnum mosses in regulating production and respiration fluxes in different environmental conditions is crucial to improve predictions of northern peatland carbon cycle‐climate feedbacks.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Variations in Ecosystem‐Scale Methane Fluxes Across a Boreal Mire Complex Assessed by a Network of Flux Towers - Koffi Dodji Noumonvi; Mats B. Nilsson; Joshua L. Ratcliffe; Mats G. Öquist; Natascha Kljun; Johan E. S. Fransson; Järvi Järveoja; Anders Lindroth; Gillian Simpson; Jacob Smeds; Matthias Peichl (Global Change Biology, 2025)
High latitude mires are key ecosystems in the context of climate change since they store large amounts of carbon while constituting an important natural source of methane (CH 4 ). However, while a growing number of studies have investigated methane fluxes (FCH 4 ) at the plot‐ (~1 m 2 ) and ecosystem‐scale (~0.1–0.5 km 2 ) across the boreal biome, variations of FCH 4 magnitudes and drivers at the mesoscale (i.e., 0.5–20 km 2 ) of a mire complex are poorly understood. This study leveraged a network of four eddy‐covariance flux towers to explore the spatio‐temporal variations in ecosystem‐scale FCH 4 across a boreal mire complex in northern Sweden over 3 years (2020–2022). We found a consistent hierarchy of drivers for the temporal variability in FCH 4 across the mire complex, with gross primary production and soil temperature jointly emerging as primary controls, whereas water table depth had no independent effect. In contrast, peat physical and chemical properties, particularly bulk density and C:N ratio, were identified as significant baseline constraints for the spatial variations in FCH 4 across the mire complex. Our observations further revealed that the 3‐year mean annual FCH 4 across the mire complex ranged from 7 g C m −2 y −1 to 11 g C m −2 y −1 , with a coefficient of variation of 16% that is similar to the variation observed among geographically distant mire systems and peatland types across the boreal biome. Thus, our findings highlight an additional source of uncertainty when scaling information from single‐site studies to the mire complex scale and beyond. Furthermore, they suggest an urgent need for peatland ecosystem models to resolve the mesoscale variations in FCH 4 at the mire complex level to reduce uncertainties in the predictions of peatland carbon cycle‐climate feedbacks.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Cross-sectoral interactions of adaptation and mitigation measures - Pam M. Berry; Sally Brown; Minpeng Chen; Areti Kontogianni; Olwen Rowlands; Gillian Simpson; Michalis Skourtos (Climatic Change, 2015)

Differential Control of Head Blight Pathogens of Wheat by Fungicides and Consequences for Mycotoxin Contamination of Grain - Duncan R. Simpson; Gillian E. Weston; Judith A. Turner; Philip Jennings; Paul Nicholson (European Journal of Plant Pathology, 2001)